Can Chess Ever Be Solved (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Data Science and Artificial Intelligence have been all over the world lately,in almost every possible field be it finance,education,entertainment,healthcare,astronomy, astrology, and many more sports is no exception. With so much data, statistics, and analysis available in this particular field, when everything is being recorded it has become easier for team selectors, broadcasters, audience, sponsors, most importantly for players themselves to prepare against various opponents. Even the analysis has improved over the period of time with the evolvement of AI, not only analysis one can even predict the things with the insights available. This is not even restricted to this,nowadays players are trained in such a manner that they are capable of taking the most feasible and rational decisions in any given situation. Chess is one of those sports that depend on calculations, algorithms, analysis, decisions etc. Being said that whenever the analysis is involved, we have always improvised on the techniques. Algorithms are somethingwhich can be solved with the help of various software, does that imply that chess can be fully solved,in simple words does that mean that if both the players play the best moves respectively then the game must end in a draw or does that mean that white wins having the first move advantage. Let’s figure it out.